Surabaya Arts Center: A Formation of Musical Orchestration Taste in Balai Pemuda (Youth Hall) - Wardhana, Muhammad Kusuma; Young, Yoongjun (Institut Seni Indonesia Surakarta, 2021)
AbstractThis research aims to understand how taste can be formed and developed from a musical arts community called Pusat Olah Seni Surabaya (POSS). This community always holds practices in musical arts in the Balai Pemuda area. The study applied Bourdieu's concept of thinking about taste. Pierre Bourdieu first revealed this concept in his book “Distinction: A Social Critique of Judgement of Taste”, which explains how a person's social strata can be judged by which society he or she comes from and refutes a notion that pure subjective truth will never exist because the truth will always be dialectical. The findings show that by using Pierre Bourdieu's aesthetic taste, formed through the aspects of habitus, capital, and the realm contained in this phenomenon. The researcher sees POSS activity attempt to build a taste for music orchestration as a form of resistance from the lower class to upper-class culture.Keywords: Habitus; Capital; Domain; Taste; Subculture